The only thing worth dying for how eleven Green Berets forged a new Afghanistan - Blehm, Eric (New York Harper, 2010)
The author exposes the realities of unconventional warfare and nation-building in Afghanistan in this chronicle of one of the most important military mission in the early days of the Global War on Terror--ODA 574--wherein a Special Forces team infiltrated the mountains of southern Afghanistan, fomented a tribal revolt, and forced the Taliban to surrender.
A most dangerous mission -- The quiet professionals -- To war -- The soldier and the statesman -- The Taliban patrol -- The battle of Tarin Kowt -- Credibility -- Madness -- Death on the horizon -- The ruins -- The thirteenth sortie -- Futility -- Rescue at Shawali Kowt -- Worth dying for.
Includes bibliographical references.
Keywords: Karzai, Hamid -- 1957-.; United States. -- Army. -- Special Forces -- History -- 21st century; Afghan War, 2001- -- Commando operations -- United States; Afghanistan -- Politics and government -- 2001-.